Long-term survivor of primary malignant melanoma of the esophagus treated with surgical resection - Sabat, Joseph (Int J Surg Case Rep, 2014)
INTRODUCTION: Primary malignant melanoma of the esophagus is a rare diagnosis with only a few hundred cases reported in the literature. Due to the aggressive nature of this disease, long-term survivors are exceedingly rare with only a handful of case reports. PRESENTATION OF CASE: We report the case of a 38 year old man who presented with chest and back pain. Workup revealed a mediastinal mass and the patient was diagnosed with primary malignant melanoma of the esophagus and treated with radical resection. Despite the poor prognosis associated with primary malignant melanoma of the esophagus, he remains disease free for over 7 years. DISCUSSION: Initially primary malignant melanoma of the esophagus was a controversial diagnosis until the demonstration of normal melanocytes in healthy patients. It is an aggressive disease that is nearly uniformly fatal. Review of the literature shows that treatment with radical surgical resection extends prognosis by months while treatment with adjuvant chemotherapy is controversial. CONCLUSION: Primary malignant melanoma of the esophagus is a rare and aggressive disease that should be treated with surgical resection when feasible. We report the rare case of a long term survivor over 7 years since diagnosis.